Optimalisasi Pesan Moderasi Beragama di Era Digital: Studi Website NU Online - Fanshoby, Muhammad; Hidayah, Khofifah Nur (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2024)
This research focuses on optimizing religious moderation messages through Search Engine Optimization (SEO) on NU Online, an Islamic website platform in Indonesia. Using a constructivist paradigm with a descriptive qualitative approach, this study explores howreligious moderation messages are constructed and disseminated through ComputerMediated Communication (CMC) and SEO. Data was collected through interviews, observations, and documentation, with a specific analysis on the popular article titled